2023
DOI: 10.3389/fpls.2023.1119670
|View full text |Cite
|
Sign up to set email alerts
|

Extreme temperature events reduced carbon uptake of a boreal forest ecosystem in Northeast China: Evidence from an 11-year eddy covariance observation

Abstract: Boreal forests, the second continental biome on Earth, are known for their massive carbon storage capacity and important role in the global carbon cycle. Comprehending the temporal dynamics and controlling factors of net ecosystem CO2 exchange (NEE) is critical for predicting how the carbon exchange in boreal forests will change in response to climate change. Therefore, based on long-term eddy covariance observations from 2008 to 2018, we evaluated the diurnal, seasonal, and interannual variations in the borea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…It is generally agreed that in most ecosystems, radiation acts as the main regulating factor for NEE on a half-hourly scale (Baldocchi, 2014;Wang et al, 2019;Yan et al, 2023). However, certain studies have suggested that the two most important factors controlling carbon exchange in grassland ecosystems are temperature and water (Kim and Verma, 1990;Xue et al, 2014).…”
Section: Constraints On Neementioning
confidence: 99%
“…It is generally agreed that in most ecosystems, radiation acts as the main regulating factor for NEE on a half-hourly scale (Baldocchi, 2014;Wang et al, 2019;Yan et al, 2023). However, certain studies have suggested that the two most important factors controlling carbon exchange in grassland ecosystems are temperature and water (Kim and Verma, 1990;Xue et al, 2014).…”
Section: Constraints On Neementioning
confidence: 99%
“…The temperature effect on NEE and LE fluxes during the warm season did not differ significantly between boreal and temperate forests, with similar controlling mechanisms involved. Under positive temperature anomalies, it may be determined by suppressed assimilation processes due to high temperature and insufficient soil moisture [70][71][72], as well as a higher decomposition rate of soil organic matter and higher autotrophic respiration [21]. Under negative temperature anomalies, it may be caused by a large reduction in GPP at lower temperatures [73].…”
Section: Variation In Nee and Le Flux In Warm Seasonmentioning
confidence: 99%
“…The above-mentioned limitations could be overcome using eddy covariance (EC). This technique, largely used in atmospheric and environmental science to determine trace gases exchanges over anthropic and natural ecosystems including urban areas [ 15 , 16 ], agricultural systems [ [17] , [18] , [19] ], grasslands [ 20 , 21 ], and forests [ 22 , 23 ], can provide continuous and automated measurements over long periods. Also, EC does not affect in depth and surface soil conditions, thus reducing uncertainties in the fluxes measured from landfill.…”
Section: Introductionmentioning
confidence: 99%